Thalidomide and Phosphodiesterase 4 Inhibitors as Host Directed Therapeutics for Tuberculous Meningitis: Insights From the Rabbit Model - Kumar, Ranjeet; Kolloli, Afsal; Singh, Pooja; Vinnard, Christopher; Kaplan, Gilla; Subbian, Selvakumar (Frontiers in Cellular and Infection Microbiology, 2020)
Tuberculous meningitis (TBM) is the most devastating form of extrapulmonary Mycobacterium tuberculosis infection in humans. Severe inflammation and extensive tissue damage drive the morbidity and mortality of this manifestation of tuberculosis (TB). Antibiotic treatment is ineffective at curing TBM due to variable and incomplete drug penetration across the blood-brain barrier (BBB) and blood-cerebrospinal fluid (CSF) barriers. Adjunctive corticosteroid therapy used to dampen the inflammation, and the pathologic manifestation of TBM improves overall survival but does not entirely prevent the morbidity of the disease and has significant toxicities, including immune-suppression. The rabbit has served as a fit for purpose experimental model of human TBM since the early 1900s due to the similarity in the developmental processes of the brain, including neuronal development, myelination, and microglial functions between humans and rabbits. Consistent with the observations made in humans, proinflammatory cytokines, including TNF-α, play a critical role in the pathogenesis of TBM in rabbits focusing the attention on the utility of TNF-α inhibitors in treating the disease. Thalidomide, an inhibitor of monocyte-derived TNF-α, was evaluated in the rabbit model of TBM and shown to improve survival and reduce inflammation of the brain and the meninges. Clinical studies in humans have also shown a beneficial response to thalidomide. However, the teratogenicity and T-cell activation function of the drug limit the use of thalidomide in the clinic. Thus, new drugs with more selective anti-inflammatory properties and a better safety profile are being developed. Some of these candidate drugs, such as phosphodiesterase-4 inhibitors, have been shown to reduce the morbidity and increase the survival of rabbits with TBM. Future studies are needed to assess the beneficial effects of these drugs for their potential to improve the current treatment strategy for TBM in humans.